Relation between Silver Nanoparticle Formation Rate and Antioxidant Capacity of Aqueous Plant Leaf Extracts - Azat Akbal; M. Haluk Turkdemir; Ahmet Cicek; Bulent Ulug (Journal of Spectroscopy)
Correlation between the antioxidant capacity and silver nanoparticle formation rates of pomegranate (Punica granatum), quince (Cydonia oblonga), chestnut (Castanea sativa), fig (Ficus carica), walnut (Juglans cinerea), black mulberry (Morus nigra), and white mulberry (Morus alba) leaf extracts is investigated at a fixed illumination. Silver nanoparticles formed in all plant leaf extracts possess round shapes with average particle size of 15 to 25 nm, whereas corresponding surface plasmon resonance peak wavelengths vary between 422 nm and 451 nm. Cupric reducing antioxidant capacity technique is used as a reference method to determine total antioxidant capacity of the plant leaf extracts. Integrated absorbance over the plasmon resonance peaks exhibits better linear relation with antioxidant capacities of various plant leaf extracts compared to peak absorbance values, with correlation coefficient values of 0.9333 and 0.7221, respectively.